Design of a Phase 3, Global, Multicenter, Randomized, Placebo-Controlled, Double-Blind Study of Nipocalimab in Pregnancies at Risk for Severe Hemolytic Disease of the Fetus and Newborn - Komatsu, Yosuke; Verweij, E.J.T. Joanne; Tiblad, Eleonor; Lopriore, Enrico; Oepkes, Dick; Agarwal, Prasheen; Lam, Edwin; Leu, Jocelyn H.; Ling, Leona E.; Nelson, Robert M.; Olusajo, Victor; Saeed-Khawaja, Shumyla; Tjoa, May Lee; Zhou, Jie; Amin, Umair; Sirah, Waheeda; Moise, Kenneth J. (American Journal of Perinatology, 2024)
Nipocalimab is a neonatal fragment crystallizable (Fc) receptor (FcRn)—blocking monoclonal antibody that inhibits placental immunoglobulin G (IgG) transfer and lowers circulating maternal IgG levels. In an open-label, single-arm, phase 2 study, nipocalimab demonstrated evidence of safety and efficacy that support further investigation in a pivotal phase 3 trial of recurrent hemolytic disease of the fetus and newborn (HDFN). The phase 3 AZALEA study aims to evaluate the efficacy and safety of nipocalimab in a larger population at risk for severe HDFN, defined as HDFN associated with poor fetal outcomes or neonatal death.AZALEA is a multicenter, randomized, placebo-controlled, double-blind, phase 3 study enrolling alloimmunized pregnant individuals (N ≈ 120) at risk for severe HDFN based on obstetric history. Participants are randomized 2:1 to receive intravenous 45 mg/kg nipocalimab or placebo weekly from 13–16 to 35 weeks gestational age (GA). During the double-blind treatment period, participants receive standard-of-care weekly monitoring for fetal anemia until planned delivery at 37 to 38 weeks of GA. Postnatal follow-up periods are 24 weeks for maternal participants and 104 weeks for neonates/infants.The primary endpoint is the proportion of pregnancies that do not result in intrauterine transfusion (IUT), hydrops fetalis, or fetal loss/neonatal death from all causes. Key secondary endpoints include the severity of HDFN as measured by a composite HDFN severity index, the earliest time to occurrence of IUT or hydrops fetalis, the modified neonatal mortality and morbidity index in liveborn neonates, and the number of IUTs received. Other endpoints are safety, patient- and caregiver-reported outcomes, pharmacokinetics, pharmacodynamics (e.g., IgG, FcRn receptor occupancy), and immunogenicity of nipocalimab.AZALEA, the first placebo-controlled, randomized, multicenter, prospective trial in severe HDFN, is designed to evaluate the safety and efficacy of nipocalimab, a potential preventive and noninvasive intervention, in at-risk HDFN pregnancies.
Keywords: neonatal Fc receptor blocker; nipocalimab; hemolytic disease of the fetus and newborn; HDFN; intrauterine transfusion; red blood cell alloimmunization; safety; efficacy; study design